Carcass and meat parameters in Cornigliese sheep breed as affected by sex and age-class. Issue 1 (2nd January 2016) - Sabbioni, Alberto; Beretti, Valentino; Zambini, Ernesto M.; Superchi, Paola
Abstract: A total of 72 animals from Cornigliese sheep breed were reared under homogeneous conditions, with the aim to assess the effect of sex (males, females) and age-class (heavy lambs, adults) on carcass and meat parameters. A model with fixed effects of herd, sex, slaughtering session, age-class and interaction (sex*age-class) was used; for slaughter data, the carcass weight was used as a covariate. The age-class effect was significant for most of the carcass measurements, indicating a late development in animals. Also, slaughter performance was significantly affected by age-class, with higher values ( p <0.05) of hot carcass yield shown by heavy lambs than by adults. Carcass compactness index was lower in heavy lambs than in adults ( p <0.001), and the lowest value (0.283; p <0.05) appeared in female heavy lambs. The percentage of fat trimmings in carcass and the tissue composition of sample cut were influenced by a significant interaction between age-class and sex ( p <0.05): in males the age-class never affected the tissue composition of sample cut, as in females the muscle and fat percentages increased with age while the bone percentage decreased. The fat content of loin meat increased with age in females ( p  < 0.05) and decreased in males ( p  < 0.05). The poly-unsaturated fatty acids (FA) content of loin meat was higher in males than in females ( p  < 0.001), with saturated FA and mono-unsaturated FA revealing significant interactions between age-class and sex ( p  < 0.05). In conclusion, future implementation of genetic selection, oriented towards the improvement of meat production characteristics that are potentially present in the breed, is important.